Development of a Motion Graphic Video about Balanced Nutrition during Pregnancy as an Educational Media for Pregnant Women - Noviyanti, Asri; Jasmi, Jasmi (Institute Of Computer Science (IOCS), 2024)
This motion graphic video educational media was developed by applying multimedia principles. In this way, this motion graphic video can be used by pregnant women as an effort to increase the knowledge and attitudes of pregnant women regarding consumption patterns during pregnancy and can reduce the incidence of complications in pregnancy and childbirth. The research design used was the Research and Development (R&D) method. This research was conducted from February 2023 to November 2023. The sample in this study was 1 material expert, 1 media expert, and 26 pregnant women. Research sampling was carried out using purposive sampling. The research method used in this research is the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). Based on the research results, it can be concluded as follows: The results of the motion graphic video feasibility test about balanced nutrition during pregnancy were declared very feasible by media experts with a score of 92%, by material experts with a score of 96%, by pregnant women with a score of 87.3%. otion graphics can be useful as an educational media,because motion graphics are combination of visual-based pieces of design or animation that combine film language.